Tarekat Qadiriyah: Pelopor Aliran-aliran Tarekat di Dunia Islam - Amsal Bakhtiar (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
This writing comprehensively reviews the Qadiriyya Sufi order, which holds significant influence. The article not only explores the biography of its founder, Sheikh 'Abd al-Qādir Jīlānī, but also delves into the teachings and practices of the Qadiriyya order. Furthermore, the article discusses the impact and the process of the spread of the Qadiriyya order in Indonesia.